TRICKY ONE

Algebra Level 3

if (x+1/x)=(-1) then find the value of( x^7+x^2+1),,,,


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Kenny Lau
Dec 7, 2014

x + 1 x = 1 x 2 + 1 = x x 2 + x + 1 = 0 —(1) ( x 1 ) ( x 2 + x + 1 ) = 0 x 3 1 = 0 x 3 = 1 —(2) \begin{array}{rcl} x+\frac1x&=&-1\\ x^2+1&=&-x\\ x^2+x+1&=&0&\mbox{---(1)}\\ (x-1)(x^2+x+1)&=&0\\ x^3-1&=&0\\ x^3&=&1&\mbox{---(2)} \end{array} x 7 + x 2 + 1 = x 3 x 3 x + x 2 + 1 = x + x 2 + 1 from (2) = x 2 + x + 1 = 0 from (1) \begin{array}{cl} &x^7+x^2+1\\ =&x^3x^3x+x^2+1\\ =&x+x^2+1&\mbox{from (2)}\\ =&x^2+x+1\\ =&\fbox0&\mbox{from (1)} \end{array}

Ashrene Roy
Sep 21, 2014

it can be done using complex cube root of unity. x^2+x+1=0.put x=w (where w^3=1) therefore w^7 +w^2 +1=w^1+w^2 +1 and w^1+w^2 +1=0 .therefore answer is 0.

Ninad Akolekar
Sep 7, 2014

This is an easier solution to the problem: x + 1/x = -1 Thus, x^2 +1 = -x. Thus, required = x^7 + x^2 -1 = x(x^6 - 1). Now, x^2 +1 = -x x^2 +x +1 = 0 Multiply both sides by (x-1). (x-1)(x^2 +x +1) = 0 x^3 - 1 =0 x^3 =1 x^6 =1

Thus, required = x^7 + x^2 -1 = x(x^6 - 1) = 0.

No need to factorize or use long division. Even we can use the concept of complex roots of unity to get the result.

Ninad Akolekar - 6 years, 9 months ago
Ankush Gogoi
Aug 3, 2014

x+ 1/x=-1. so x^2 + x +1=0...divide (x^7 + x^2 +1) by (x^2 +x+1) using long division...so we get quotient=x^5 - x^4 + x^2 -x+1 and remainder 0...Using divident=(divisor * quotient)+remainder, we get x^7 + x^2 +1=(x^2 + x+1)*(x^5 - x^4 + x^2 -x+1) + 0....since x^2 + x +1=0 therefore x^7 + x^2 +1=0...

Sounak Guha
Jul 29, 2014

1 st thing is u have to factorize it ,,,,( x^7-x^4)+(x^4+x^2+1),,,,then take the common term (x^2+x+1),, whose value is 0 ,,,as stated in the question ,,,,so the answer is zero x^4(x^3-1) + (x^4+2 x^2+1-x^2) {x^4(x-1)(x^2+x+1)} + {(x^2+x+1)(x^2-x+1)} (x^2+x+1) {x^4(x-1)+(x^2-x+1)} = 000

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...